Ensemble seismic study of the properties of the core of red clump stars - Noll, Anthony; Basu, Sarbani; Hekker, Saskia (Astronomy and astrophysics, 2025)
Context. Red clump (RC) stars still pose open questions regarding several physical processes, such as the mixing around the core or the nuclear reactions, which are ill-constrained by theory and experiments. The oscillations of RC stars, which are of a mixed gravito-acoustic nature, allow us to directly investigate the interior of these stars and thereby better understand their physics. In particular, the measurement of their period spacing is a good probe of the structure around the core. Aims. We aim to explain the distribution of period spacings in RC stars observed by Kepler by testing different prescriptions of core-boundary mixing and the nuclear reaction rate. Methods. Using the MESA stellar evolution code, we computed several grids of core-helium-burning tracks, with varying masses and metallicities. Each of these grids has been computed assuming a certain core boundary mixing scheme, or 12 C(α,γ) 16 O reaction rate. We then sampled these grids, in a Monte-Carlo fashion, using observational spectroscopic metallicity and seismic mass priors, in order to retrieve a period spacing distribution, which we compared to the observations. Results. We find that the best-fitting distribution is obtained when using a “maximal overshoot” core-boundary scheme, which has similar seismic properties as a model whose modes are trapped outside a semi-convective region, and which does not exhibit core-breathing pulses at the end of the core-helium-burning phase. If no mode trapping is assumed, then no core boundary mixing scheme is compatible with the observations. Moreover, we find that extending the core with overshoot worsens the fit. Additionally, reducing the 12 C(α,γ)16 O reaction rate (by around 15%) improves the fit to the observed distribution. Finally, we note that an overpopulation of early RC stars with period spacing values around 250 s is predicted by the models but not found in the observations.Conclusions. Assuming a semi-convective region and mode trapping, along with a slightly lower than nominal 12 C(α,γ) 16 O rate, allowed us to reproduce most of the features of the observed period spacing distribution, except for those of early RC stars.